Whole genome characterization of thermophilic Campylobacter species isolated from dairy manure in small specialty crop farms of Northeast Ohio - Deblais, Loic; Jang, Hyein; Kauffman, Mike; Gangiredla, Jayanthi; Sawyer, Marianne; Basa, Saritha; Poelstra, Jelmer W.; Babu, Uma S.; Harrison, Lisa M.; Hiett, Kelli L.; Balan, Kannan V.; Rajashekara, Gireesh (Frontiers in Microbiology, 2023)
With society looking more to consuming locally grown produce, small specialty crop farms (SSCF) are a viable and growing segment of the food production chain in the U.S. The goal of this study was to investigate the genomic diversity of Campylobacter isolated from dairy manure (n=69) collected from ten SSCF in Northeast Ohio between 2018 and 2020. A total of 56 C. jejuni and 13 C. coli isolates were sequenced. Multi-locus sequence typing (MLST) identified 22 sequence types (ST), with ST-922 (18%) and ST-61 (13%) predominant in C. jejuni and ST-829 (62%) and ST-1068 (38%) predominant in C. coli. Interestingly, isolates with similar genomic and gene contents were detected within and between SSCF over time, suggesting that Campylobacter could be transmitted between farms and may persist in a given SSCF over time. Virulence-associated genes (n=35) involved in the uptake and utilization of potassium and organic compounds (succinate, gluconate, oxoglutarate and malate) were detected only in the C. jejuni isolates, while 45 genes associated with increased resistance to environmental stresses (capsule production, cell envelop integrity, and iron uptake) were detected only in the C. coli isolates. C. coli isolates were also sub-divided into two distinct clusters based on the presence of unique prophages (n=21) or IncQ conjugative plasmid/type-IV secretion system genes (n=15). C. coli isolates harbored genes associated with resistance to streptomycin (aadE-Cc; 54%) and quinolone (gyrA-T86I; 77%), while C. jejuni had resistance genes for kanamycin (aph3’-IIIa; 20%). Both species harbored resistance genes associated with -lactam (especially, BlaOXA-193; up to 100%) and tetracycline (tetO; up to 59%). Our study demonstrated that Campylobacter genome plasticity associated with conjugative transfer might provide resistance to certain antimicrobials and viral infections via the acquisition of protein-encoding genes involved in mechanisms such as ribosomal protection and capsule modification.